Hepatoblastoma with precocious puberty - Enono Yhoshu; Yasir A Lone; Jai K Mahajan; Umesh Bahadur Singh (Wolters Kluwer Medknow Publications, 2019)
Hepatoblastoma (HB), a primary liver tumor of childhood, is often accompanied by raised levels of alpha-fetoprotein (α-FP). Rarely, the beta-human chorionic gonadotropin (β-hCG) levels may also be elevated, which can cause peripheral precocious puberty (PPP). We report a case of HB with precocious puberty wherein hormonal assays showed an increase in α-FP, β-hCG, and testosterone levels, and suppression of follicle-stimulating and luteinizing hormone levels. After chemotherapy and surgery, α-FP, β-hCG, and testosterone levels normalized, and the signs of virilization did not progress further. New therapeutic approaches have made a previously reported grim prognosis of virilizing HB, more favorable now. In the assessment of PPP, the possibility of a tumoral source for the hormones should also be considered.